Evaluating The Frequency Of Additive Retentive Features By Dental Students During Tooth Preparation For Fixed Partial Dentures - An Institution Based Retrospective Study - SRI, DR. HARINI; AHMED, DR. NABEEL; SASANKA, DR. L.KEERTHI (The journal of contemporary issues in business and government, 2021)
Aim:The aim of this study was to retrospectively evaluate the frequency of additional retentive features used during tooth preparation for Fixed Partial Dentures by the dental students and to determine preference of retentive features in each sextant. Method:The data for this study was collected from June 2019 to March 2020 after taking ethical clearance from the Institutional Review Committee. A total of 999 case records of the patients who received fixed partial denture in a dental institution at Chennai was included. The data regarding the tooth preparation was collected from the case record. SPSS 20 version was used for statistical analysis. Chi-square test was applied to see association between the retentive features and tooth location. Result:The study reported that 30.7% of tooth preparation had proximal boxes; 14.8% had grooves; 18.7% had occlusal offset and 35.7% did not incorporate any additional retentive feature. Association between the retentive features and location of the tooth was found to be statistically significant. Conclusion:Most of the dental students did not prefer additional retentive features followed by proximal box, grooves and occlusal offset. Association between the retentive features and location of the tooth was found to be statistically significant with p value of 0.02. In sextant 1, 5 and 6 no additional retentive features were preferred. In sextant 2 and 4, proximal box was highly preferred. In sextant 3, both proximal box and no additional retentive feature was equally preferred.